2008
DOI: 10.1002/anie.200705314
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective 1,3‐Dipolar Cycloaddition of Nitrones with Ethyl Vinyl Ether: The Difference between Brønsted and Lewis Acid Catalysis

Abstract: Brønsted and Lewis face off: A new chiral N‐triflyl phosphoramide is used for asymmetric 1,3‐dipolar cycloaddition of diaryl nitrones to ethyl vinyl ether to give the endo products in up to 93 % ee (see scheme; Tf=trifluoromethanesulfonyl; Ad=adamantyl). The structure of the chiral phosphoramide was confirmed by X‐ray crystallographic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 191 publications
(71 citation statements)
references
References 56 publications
(16 reference statements)
2
67
0
2
Order By: Relevance
“…The L-phenylalanine-based 1,1¢-binaphthyl-2,2¢-diamine (BINAM) catalyst 194, with trifluoromethanesulfonic acid as an additive, afforded the optimal results with good endo-diastereoselectivity and enantioselectivity up to 95% ee. [80]. Only 5 mol% of this air-stable catalyst was used, and the reactions were completed within 1 h. The endo-selectivity of this cycloaddition is different to the previously reported exo-selectivity of the aluminum-catalyzed reaction (Lewis acid catalysis).…”
Section: [3 + 2] or 13-dipolar Cycloadditionmentioning
confidence: 64%
“…The L-phenylalanine-based 1,1¢-binaphthyl-2,2¢-diamine (BINAM) catalyst 194, with trifluoromethanesulfonic acid as an additive, afforded the optimal results with good endo-diastereoselectivity and enantioselectivity up to 95% ee. [80]. Only 5 mol% of this air-stable catalyst was used, and the reactions were completed within 1 h. The endo-selectivity of this cycloaddition is different to the previously reported exo-selectivity of the aluminum-catalyzed reaction (Lewis acid catalysis).…”
Section: [3 + 2] or 13-dipolar Cycloadditionmentioning
confidence: 64%
“…27 We extended the utility of N tri yl oxo phosphoramide to the enantioselective 1,3 dipolar cycloaddition of nitrones with ethyl vinyl ether. 26 It should be noted that in sharp contrast to the exo selectivity of Lewis acid catalyzed cycloaddition of diaryl nitrones with alkyl vinyl ether reported by Jørgensen and co workers, 28 this N tri yl oxo phosphoramide catalyzed cycloaddition reaction gave the desired product with high endo selectivity (Scheme 13). The dramatic difference in diastereoselectivity between the [3 2] cycloaddition catalyzed by the Brønsted acid (up to 97% endo selective) and MeAl BINOL complex (up to 95% exo selective) can be rationalized by transition state structure (Figure 11).…”
Section: Chiral N Tri Yl Oxo Phosphoramidesmentioning
confidence: 93%
“…X ray crystallography analysis revealed that the Brønsted acid has P O bond and P N single bond and the proton is located on the N atom rather than on the O atom as shown in Figure 10. 26 We successfully applied this Brønsted acid to the catalytic asymmetric Diels Alder reaction of ethyl vinyl ketone with siloxydienes, which is the rst example of activation of carbonyl functionality in phosphoric acid catalysis. 25 Introduction of the N tri yl group dramatically increased the reactivity: N tri yl phosphoramide gave the Diels Alder adducts in excellent yields and enantioselectivities, whereas phosphoric acid showed no catalytic activity (Scheme 11 and Table 2).…”
Section: Chiral N Tri Yl Oxo Phosphoramidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has made some efforts to increase the acidity of this type of catalysts through modifying chiral phosphoric acid structure to corresponding chiral N-triflyl phosphoramide [67,68] or N-triflyl thio-and seleno-phosphoramide [56,69]. Another interesting approach for enhancing reactivities of chiral phosphoric acid catalysis has appeared recently from two independent studies, in which Lewis acid activation of Brønsted acid (LBA) consideration is the key to success.…”
Section: Lewis Acid/chiral Phosphoric Acid Combinationmentioning
confidence: 99%